Innovative energy strategies for CO₂ stabilization - Watts, Robert G (Cambridge University, 2013)
This book discusses the feasibility of increasingly efficient energy use and the potential for supplying energy from sources that do not introduce CO2. It will be essential reading for engineers/physicists, and industrial leaders and politicians. It will also be used as a supplementary textbook on advanced courses on energy.